Inactivation of Anisakis pegreffii larvae in anchovies (Engraulis encrasicolus) by salting and quality assessment of finished product. (June 2016) - Anastasio, Aniello; Smaldone, Giorgio; Cacace, Domenico; Marrone, Raffaele; Lo Voi, Andrea; Santoro, Mario; Cringoli, Giuseppe; Pozio, Edoardo
Abstract: There is an increasing reporting of Anisakiasis in humans at the world level and this disease has become a concern for the public health and for the fish and derived product trade. Humans acquire the infection by the ingestion of live larvae present in raw or almost raw (e.g., marinate, salted) fish products if the processing is insufficient to devitalize the worms. The aim of this study was to asses a dry salting process in killing Anisakis pegreffii larvae in naturally infected European anchovies ( Engraulis encrasicolus ) and to evaluate the quality assessment. The results show that a dry salting process with a salt concentration of 21% in all parts of the anchovy fillets devitalize A. pegreffii larvae in a 15 day period. The finished product showed a good panel acceptance and anchovies reached a good quality grade. Highlights: Anisakiasis is an important food-borne disease due to the consumption of raw fish. A 21% salt concentration kills Anisakis pegreffii larvae in fish fillets in 15 days. Salting process causes structural damage of the A. pegreffii larval cuticle.